Smartphone‐based colorimetric chiral recognition of ibuprofen using aptamers‐capped gold nanoparticles. Issue 3 (15th December 2017) - Ping, Jing; He, Zhenjiang; Liu, Jianshe; Xie, Xuehui
Abstract: Sensitive and fast detection of ibuprofen enantiomers is very critical for required routine monitoring and risk assessment of trace pollutants in water samples. Here a simple, rapid and highly sensitive android smartphone application for chiral recognition was developed. Aptamer‐capped gold nanoparticles (AuNPs) was demonstrated as an efficient detection platform for (S)‐(+)‐ibuprofen (S‐Ibu) and (R)‐(‐)‐ibuprofen (R‐Ibu). Detachment of an enantioselective aptamer from the AuNPs surface and binding with an enantiomer of Ibu lead to AuNPs aggregation, which allows a rapid enantiodiscrimination of Ibu by monitoring the absorbance changes of AuNPs solution in the UV‐vis spectrum. Under optimal conditions, the limit of detection for S‐Ibu and R‐Ibu was 1.24 and 3.91 pg/mL, respectively. These probes showed good chiral recognition ability in mixed samples (i.e. S‐Ibu + R‐Ibu) and environmental samples. These advantages can be further developed by quantitative measurement with smartphone, which opens new opportunities for on‐site detection of trace chiral pollutants in a simple and practical manner.